Representações das paisagens do Cerrado (MT) na iconografia do artista Benedito Nunes - Bessa, Jonas de Alves (2023)
The general objective of the present work is to study the representations of the cerrado landscapes based on Benedito Nunes' Iconography, having as object of analysis the iconographic collection of the artist, who produced a wide range of paintings about the cerrado, especially in the State of Mato Grosso. The following specific objectives were also defined: to understand the trajectory of Cultural Geography and its approach to the concept of landscape; to interpret the work of Benedito Nunes and the way this painter incorporated the Cerrado landscapes as inspiration for his artistic production, in an approach on the geography of images; to observe how geography and art can dialogue based on concepts common to both sciences. The choice of the artist to develop this research happened due to the relevance of his works, which represented many rural and urban landscapes of the Cerrado. To this end, the methodology used in this research was divided into three stages: in the first stage, the bibliographic review and the document analysis necessary for the construction of the theoretical referential were carried out. Still in this methodological stage, the life and work trajectory of the artist Benedito Nunes was discussed. For the analysis and interpretation of the images of the referred artist within the perspective of geography, the Iconographic analysis and Iconology of the Images of the works of Art. This theory propitiated the interpretation of the works of Benedito Nunes, under a geographic bias of Interpretations, which sought to identify the spatiality of the elements by means of iconography. The fieldwork carried out in the city of Cuiabá (MT) was the second stage of the research, and enabled the achievement of the proposed objectives through the collection of empirical data (interviews and photographs). The third and last stage was characterized by the interpretation of the collected data, theoretical discussions, and the final production of the dissertation. We conclude, therefore, that from the theoretical point of view, Geography has produced many studies based on the concept of Landscape and Cultural Geography. It was found that the concept of Landscape was, in fact, adequate for this research, since the artist chosen for the case study represented much of his iconography in the form of paintings of landscapes of the Cerrado of Mato Grosso.